ASSESSING ORGANIZATIONAL MATURITY IN PUBLIC SERVICE AGENCIES: EVIDENCE FROM BASIC SERVICE DELIVERY IN KUPANG REGENCY, INDONESIA - Kusmana, Dedi; Ismunarta, Ismunarta; Sari, Agni (CosmoGov: Jurnal Ilmu Pemerintahan, 2025)
This study assesses the organizational maturity of local government agencies (OPD) responsible for mandatory basic public services in Kupang Regency, Indonesia. This issue matters because empirical, structured maturity assessments of basic-service agencies remain limited, making it difficult for local governments to pinpoint which organizational capacities most urgently require improvement. The study covers six agencies: the Departments of Education, Health, Public Works and Spatial Planning, Housing–Settlement Areas and Land Affairs, Municipal Police and Fire Services, and Social Affairs. Using a qualitative approach, data were collected through in-depth interviews and document reviews in March 2024. Maturity was evaluated using 11 variables specified in Ministry of Home Affairs Regulation (Permendagri) No. 99/2018. The results indicate that organizational maturity in Kupang Regency remains low, with an overall score of 19.66 in 2022, increasing to 21.16 in 2023. The key finding is that seven variables consistently scored low across agencies: service quality assurance, service standard operating procedures, staff education and training, equipment resource management, risk management, service innovation development, and organizational culture.gb777